States and the management of the international mobility highly skilled labour in the age of neoliberalism. (2017) - Pellerin, HélÁ¨ne
Very few studies analyse the political economy of programs that OECD states have adopted to recruit and attract temporarily international highly skilled workers and professionals. These programs situated outside of traditional temporary foreign workers schemes, are not solely determined by economic globalisation and the liberalisation of trade in services. The role of the state in constructing the conditions of international mobility, and the relation between international mobility programs and labour market management need to be examined. This article provides an initial foray into the political economy of international mobility programs. As the Canadian case demonstrates, the state is actively involved through international mobility programs in the facilitation of economic liberalisation and competitiveness, in shaping the international mobility of highly skilled foreign workers, as well as promoting labour market flexibility in the knowledge economy.